HOLDFAST PADA INSOLE SEPATU HAND WELTED DI CV. RAVABIA KREASI NUSANTARA BANDUNG – JAWA BARAT - Halim Abdur Rahman; Anwar Hidayat (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2020)
CV. Ravabia Kreasi Nusantara Bandung West Java is the one company that produced traditional shoes, such as handmade leather shoe and have a good and strong construction. The problem found in the hand welted type of shoe, when lasting the upper is still loose and less tight with the shoelast proportion on the part of the palm. Method of finding solutions by means of experiment the insole of hand welted shoe. Then analyze existing data with literature studies and shoe making experiments about hand walted shoe. Shoe manufacture at the CV. Ravabia Kreasi Nusantara, was found a lack when lasting. The cause of factor is when the insole that have no stitch lines yet. Action taken to overcome the problems that occur is by making a stitch lines at the bottom of insole. After lasting the shoe not loose again.